Effect of Graphene Oxide Synthesis Method on Properties and Performance of Polysulfone-Graphene Oxide Mixed Matrix Membranes - Safae Sali (18112840) (2019)
Graphene oxide (GO) has shown great promise as a nanofiller to enhance the performance of mixed matrix composite membranes (MMMs) for water treatment applications. However, GO can be prepared by various synthesis routes, leading to different concentrations of the attached oxygen functional groups. In this research, GO produced by the Hummers’, Tour, and Staudenmaier methods were characterized and embedded at various fractions into the matrix of polysulfone (PSf) and used to prepare microfiltration membranes via the phase inversion process. The effects of the GO preparation method and loading on the membrane characteristics, as well as performance for oil removal from an oil-water emulsion, are analyzed. Our results reveal that GO prepared by the Staudenmaier method has a higher concentration of the more polar carbonyl group, increasing the membrane hydrophilicity and porosity compared to GO prepared by the Hummers’ and Tour methods. On the other hand, the Hummers’ and Tour methods produce GO with larger sheet size, and are more effective in enhancing the mechanical properties of the PSf membrane. Finally, all MMMs exhibited improved water flux (up to 2.7 times) and oil rejection, than those for the control PSf sample, with the optimum GO loading ranged between 0.1–0.2 wt%. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nano9050769